KUALITAS KIMIAWI DAN SENSORIS KECAP BERBAHAN BAKU KEONG SAWAH - Iin Khusnul Khotimah; Nooryantini Soetikno (Fish Scientiae, 2019)
The study aims to determine the chemical and sensory quality of soy sauce madefrom conch paddy (Bellamyâ javanica) with the addition of a protease enzyme. The processing of soy sauce is naturally takes a long time, so as to speed up the fermentation process using protease enzymes (bromelain and papain). The design is completely randomized factorial design 3x3, 2 replications. The first factor (A) addition of theenzyme bromelain (A1 = 0.5%; A2 = 1%; and A3 = 1.5%); The second factor (B) theaddition of the enzyme papain (B1 = 0.5%; B2 = 1%; and B3 = 1.5%. The parameters observed chemical quality soy sauce snail rice fields (levels of protein, fat, water andash).Quality sensory (specification of color, aroma and viscosity). Observations were made on the fermentation (5, 7, 10, and 13 days). the results show the best rice conchsauce with the addition of the enzyme bromelain enzyme papain 1.5% and 1%, fermentedfor 7 days has the highest value of 21.71% protein content, fat 2,355%; 74.275% water;ashes 9.89%; color specifications 71.25 (almost blackish brown / dark); aroma 59.67 (aroma typical fish sauce already began to smell ); and the viscosity of 73 (almost the same viscosity as commercial fish sauce).